Application of Problem-Based Worksheets to Develop Higher Order Thinking Skills In The Utilization of Coconut Shells As Zn Metal Adsorbent In Laboratory Waste - Lestari, Risma; Sukmawardani, Yulia; Subarkah, Cucu Zaenab; Farida, Ida (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study aims to analyze scientific performance and analyze students' higher-order thinking skills after the application of problem-based LK to develop higher-order thinking skills in the use of coconut shell as an adsorbent for Zn metal in laboratory wastewater. The research method used is pre-experiment with one shot case study design. The subjects in this study were chemistry education students of UIN Sunan Gunung Djati Bandung who took separation chemistry courses. The instruments used are learning descriptions, LK, and higher order thinking skills questions. Students' higher-order thinking skills are measured through working on six HOTS questions based on the concept of Bloom's taxonomy level of thinking at cognitive levels C4 (analyze), C5 (Evaluate) and C6 (Create). The results showed that the average value of student performance in solving problem-based LK was 88.35 with a very good category. The highest average score achieved was at stage 2 organizing students with a score of 91.5 and a very good category. The lowest average value at stage 4 develops and presents results with a value of 86.25 and a very good category. The results of students' higher order thinking skills obtained an average score of 78 in the good category. Thus the application of problem-based LK on the utilization of coconut shell as a heavy metal adsorbent in laboratory wastewater can develop higher order thinking skills in students.